Chekhov the Immigrant : Translating a Cultural Icon - Coles, Robert; De Sherbinin, Julie W.; Finke, Michael C., 1957- (Book collections on Project MUSE., 2007)
"Comprising the proceedings of a 2004 NEH-funded symposium marking the hundredth anniversary of Chekhov's death, Chekhov the Immigrant takes a multi-disciplinary approach to Chekhov's impact on American culture with: articles by literary scholars, contemporary authors of fiction and criticism, theater directors, and translators; transcripts of forums on translating Chekhov and Chekhov and medicine; and a DVD recording of a conversation about Chekhov with the eminent American physician and author Robert Coles"--Publisher's summary.